Comparison of nivolumab and sorafenib for first systemic therapy in patients with hepatocellular carcinoma and Child‐Pugh B cirrhosis. (2nd June 2022) - Chapin, William J.; Hwang, Wei‐Ting; Karasic, Thomas B.; McCarthy, Anne Marie; Kaplan, David E.
Abstract: Background: Patients with decompensated cirrhosis are excluded or underrepresented in clinical trials of systemic therapies for hepatocellular carcinoma (HCC) and comparisons of available therapies are lacking. We aimed to compare overall survival for patients with HCC and Child‐Pugh B cirrhosis treated with nivolumab or sorafenib as first systemic treatment. Methods: We performed a retrospective cohort study in patients with HCC and Child‐Pugh B cirrhosis treated at Veterans Affairs medical centers to compare overall survival, adverse events, and reason for discontinuation of therapy between patients treated with nivolumab or sorafenib as first systemic treatment. All statistical tests were 2‐sided. Results: Of those meeting inclusion criteria, 431 patients were treated with sorafenib and 79 with nivolumab. Median OS was 4.0 months (95% CI 3.5–4.8) in the sorafenib cohort and 5.0 months (95% CI 3.3–6.8) in the nivolumab cohort. In the multivariable Cox proportional hazards model, nivolumab was associated with a significantly reduced hazard of death compared to sorafenib (HR 0.69; 95% CI 0.52–0.91; p  = 0.008). In a secondary analysis using propensity score methods, results did not reach statistical significance (HR 0.77; 95% CI 0.55–1.06; p  = 0.11). Treatment was discontinued due to toxicity in 12% of patients receiving nivolumab compared to 36% receiving sorafenib ( p  = 0.001). Conclusion: In patients with HCC and Child‐Pugh B cirrhosis, nivolumab treatment may be associated with improved overall survival and improved tolerability compared to sorafenib and should be considered for the first systemic treatment in this population. Abstract : Patients with hepatocellular carcinoma (HCC) and Child‐Pugh B cirrhosis have poor prognosis and no comparative data exists for guideline‐directed first line systemic therapies in this patient population. In this retrospective cohort study of patients with HCC and Child Pugh B cirrhosis treated at VA medical centers, nivolumab treatment was associated with improved overall survival in multivariable analysis and less treatment discontinuation for toxicity compared to sorafenib. Nivolumab should be considered as a first systemic therapy option in this patient population.